Understanding Energy Citizenship: How Cultural Capital Shapes the Energy Transition - Sikke R. Jansma; Le Anh Nguyen Long; Dasom Lee (Energies, 2023)
Community involvement and citizenship have been crucial drivers in energy transitions worldwide. To deepen our understanding of the energy transition and to further promote energy citizenship, we leverage Bourdieu’s concept of cultural capital to shed light on the inequities in community-centered energy transition processes. More specifically, this study demonstrates that cultural capital is an important indicator of an individual’s willingness to participate in renewable energy-related behavior and social movements. Using survey data in the Netherlands as a case study, it finds that depending on the type of energy citizenship, i.e., material participation (investments) or communicative participation (protest), different types of cultural capital are in play. The results of this study imply that a nuanced approach towards both concepts, namely energy citizenship and cultural capital, is needed. The scholarly and practical implications of this study are discussed, and the study concludes with pathways for more comprehensive community engagement.